Seasonal genetic partitioning in the neotropical malaria vector, Anopheles darlingi - Angella, Aline F. [UNESP]; Salgueiro, Patricia; Gil, Luiz H. S.; Vicente, Jose L.; Pinto, Joao; Ribolla, Paulo E. M. [UNESP] (Biomed Central Ltd., 2014)
Background: Anopheles darlingi is the main malaria mosquito vector in the Amazonia region. In spite of being considered a riverine, forest-dwelling species, this mosquito is becoming more abundant in peri-urban areas, increasing malaria risk. This has been associated with human-driven environmental changes such as deforestation.Methods: Microsatellites were used to characterize A. darlingi from seven localities along the Madeira River, Rondonia (Brazil), collected in the early and late periods of the rainy season.Results: Two genetically distinct subpopulations were detected: one (subpopulation A) was associated with the late rainfall period and seems to be ecologically closer to the typical forest A. darlingi; the other (subpopulation B) was associated with the early rainfall period and is probably more adapted to drier conditions by exploiting permanent anthropogenic breeding sites. Results suggest also a pattern of asymmetric introgression, with more subpopulation A alleles introgressed into subpopulation B. Both subpopulations (and admixed mosquitoes) presented similar malaria infection rates, highlighting the potential for perennial malaria transmission in the region.Conclusions: The co-occurrence of two genetically distinct subpopulations of A. darlingi adapted to different periods of rainfall may promote a more perennial transmission of malaria throughout the year. These findings, in a context of strong environmental impact due to deforestation and dam construction, have serious implications for malaria epidemiology and control in the Amazonian region.
Keywords: Anopheles darlingi; Amazonia; Seasonal genetic structure; Microsatellites; Malaria